دور التكوين أثناء الخدمة في تحسين الخدمة الصحية دراسة ميدانية المستشفى المختلط 240سرير الأغواط - بن إبراهيم إيمان; فرحات حميدة (جامعة عمار ثليجي الاغواط, 2022)
The aim of this study is to highlight importance and role of training in health Mixed hospital 240 beds of laghouat, where training is one of the most important factors contributing to the advancement of the human element and an option to raise the banner of challenge to keep pace with scientific and technological progress , employees and their skills so that the institution can improve the performance of its workers and increase the quality of their outputs maintain the quality of their outputs on the hand , as well as provide opportunities for their workers to enable them to improve their scientific and professional level , which qualifies them for professional and social promotions on the other hand , stability and effectiveness . On this basics, we conducted a field study on a simple of the study society represented by a group of workers and workers of the Mixed hospital 240 beds of laghouat , and this study was based on descriptive methods and analytical approach In order to answer the problem presented and verify to validity of the hypotheses. A questionnaire was prepared to include a simple of the workers of a Mixed hospital 240 beds in laghouat, the number of questionnaire distributed “ 30 “ was retrieved . we have emptied it into the SPSS program of analysis . Analyzing the results obtained, we find the importance and effectiveness of the training progress adopted by institution in improving the health service.